1988
DOI: 10.1016/0736-5748(88)90034-2
|View full text |Cite
|
Sign up to set email alerts
|

DNA content in neurons of Auerbach's plexus under experimental conditions in adult rats

Abstract: Some nerve cells of the Auerbach's myenteric plexus of the intestine of the adult rat, which hypertrophied following a surgically induced stenosis, began DNA synthesis unrelated to mitotic division. The cytophotometric analysis confirmed and quantified the amount of synthesis revealed by autoradiography with tritiated thymidine uptake. Numerous nerve cells show a DNA content exceeding the diploid level. Only a few of these show twice the diploid content. The significance of the DNA synthesis is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In a series of studies, Giacobini-Robecchi and coworkers showed the presence of DNA replication (by autoradiography after 3H-thymidine administration and PCNA immuno-staining) in myenteric neurons from the small intestine loops upstream from a partial stenosis (Corvetti et al 2001;Poncino et al 1990;Giacobini Robecchi et al 1988). However, cytophotometry after Feulgen staining showed that myenteric neuron DNA replication might not be due to a tetraploid DNA content related to cell division, but instead to unscheduled DNA synthesis that leads to a hyper diploid DNA content (Poncino et al 1990;Giacobini Robecchi et al 1988). Electrophoretic analysis of total genomic DNA has also suggested that unscheduled DNA synthesis can be due to DNA amplification (Giacobini Robecchi et al 1995).…”
Section: Neural Proliferation In the Adult Pns: Challenging The Dogmamentioning
confidence: 99%
See 1 more Smart Citation
“…In a series of studies, Giacobini-Robecchi and coworkers showed the presence of DNA replication (by autoradiography after 3H-thymidine administration and PCNA immuno-staining) in myenteric neurons from the small intestine loops upstream from a partial stenosis (Corvetti et al 2001;Poncino et al 1990;Giacobini Robecchi et al 1988). However, cytophotometry after Feulgen staining showed that myenteric neuron DNA replication might not be due to a tetraploid DNA content related to cell division, but instead to unscheduled DNA synthesis that leads to a hyper diploid DNA content (Poncino et al 1990;Giacobini Robecchi et al 1988). Electrophoretic analysis of total genomic DNA has also suggested that unscheduled DNA synthesis can be due to DNA amplification (Giacobini Robecchi et al 1995).…”
Section: Neural Proliferation In the Adult Pns: Challenging The Dogmamentioning
confidence: 99%
“…Two possibilities have been tentatively proposed to explain the increase in the number of neurons during adulthood: 1) de novo neurogenesis (i.e., based on DNA replication and cell division); 2) neuron addition (i.e., late differentiation of poorly differentiated neuronal precursors without cell division) (Farel 2001;Farel 2002;Geuna et al 2000). Although the detection of DNA replication (Ciaroni et al 2000;Farel 2001;Farel 2002;Geuna et al 2000;Giacobini Robecchi et al 1988) is considered a predictor of cell division and thus de novo neurogenesis, it might also be due to selective amplification of a few DNA sequences (Corvetti et al 2001;Giacobini Robecchi et al 1995). On the other hand, the possibility that the neuron number increase is due to the late differentiation of slightly immature neurons is partially ruled out by the difficulty in identifying (even with careful electron microscope investigation) the immature neurons in adult DRGs (Geuna, unpublished).…”
Section: Neural Proliferation In the Adult Pns: Challenging The Dogmamentioning
confidence: 99%
“…Two possibilities have been tentatively proposed to explain the increase in the number of neurons during adulthood: 1) de novo neurogenesis (i.e., based on DNA replication and cell division); 2) neuron addition (i.e., late differentiation of poorly differentiated neuronal precursors without cell division) (Farel 2001;Farel 2002;Geuna et al 2000). Although the detection of DNA replication (Ciaroni et al 2000;Farel 2001;Farel 2002;Geuna et al 2000;Giacobini Robecchi et al 1988) is considered a predictor of cell division and thus de novo neurogenesis, it might also be due to selective amplification of a few DNA sequences (Corvetti et al 2001;Giacobini Robecchi et al 1995). On the other hand, the possibility that the neuron number increase is due to the late differentiation of slightly immature neurons is partially ruled out by the difficulty in identifying (even with careful electron microscope investigation) the immature neurons in adult DRGs (Geuna, unpublished).…”
Section: Neural Proliferation In the Adult Pns: Challenging The Dogmamentioning
confidence: 99%
“…In a series of studies, Giacobini-Robecchi and coworkers showed the presence of DNA replication (by autoradiography after 3H-thymidine administration and PCNA immuno-staining) in myenteric neurons from the small intestine loops upstream from a partial stenosis (Corvetti et al 2001;Poncino et al 1990;Giacobini Robecchi et al 1988). However, cytophotometry after Feulgen staining showed that myenteric neuron DNA replication might not be due to a tetraploid DNA content related to cell division, but instead to unscheduled DNA synthesis that leads to a hyper diploid DNA content (Poncino et al 1990;Giacobini Robecchi et al 1988). Electrophoretic analysis of total genomic DNA has also www.intechopen.com suggested that unscheduled DNA synthesis can be due to DNA amplification (Giacobini Robecchi et al 1995).…”
Section: Neural Proliferation In the Adult Pns: Challenging The Dogmamentioning
confidence: 99%